A rapid lithium-ion battery heating method based on bidirectional pulsed current: Heating effect and impact on battery life. (15th December 2020) - Qin, Yudi; Du, Jiuyu; Lu, Languang; Gao, Ming; Haase, Frank; Li, Jianqiu; Ouyang, Minggao
Graphical abstract: Highlights: Batteries are easily heated up at a rate of more than 10 °C/min by proposed method. The heat is mainly from ohmic and polarization resistances based on Joule's law. A rapid and effective method of testing SOH under pulsed heating is proposed. Pulsing parameters have opposite effects and sensitivity on heating and durability. Negligible impact on life: only 1% capacity loss after 170 h continuous heating. Abstract: Low temperature charging is a major challenge for lithium-ion batteries, since it could lead to dramatic performance degradation and potential safety issues. A pre-heating process is usually applied to overcome above-mentioned challenges. Pulsed operation is adopted as one of established internal pre-heating methods with good temperature uniformity. Herein we employed and investigated bidirectional pulsed current through experimental methods to obtain the main data of the thermal action for comprehensively analyzing heat generation characteristics and thermoelectric coupling model based on second-order RC circuit to verify the basic principle. Battery durability research was then conducted via a continuous heating test method which enables rapid testing of capacity degradation. The results indicated that proposed pulsed heating could not significantly damage the life span from the perspective of long-term applications: the battery has only 1% capacity decay after 170 h continuous heating with a heating rate of 11 °C/min. Parameters, which are beneficial for heating rate, are further found to be detrimental for degradation and vice versa. Nevertheless, based on the outcome of this study, the pulse waveform with a shorter period and a higher amplitude are suggested to give an optimal combination of higher heating rate and lower degradation. Such a pulsed heating method has several potential application scenarios, ranging from electric vehicles and even stationary storage systems.